In vitro and clinical evaluation of optical tooth whitening toothpastes. (December 2017) - Tao, Danying; Sun, Jianing N.; Wang, Xiaojie; Zhang, Qiong; Naeeni, Mojgan A.; Philpotts, Carole J.; Joiner, Andrew
Abstract: Objectives: To measure tooth whitening effects delivered immediately after brushing with silica-based toothpastes containing either blue covarine or a combination of blue covarine and FD&C Blue No. 1 in vitro and in vivo . Methods: Salivary pellicle coated human extracted teeth were brushed with either a slurry of a toothpaste containing blue covarine (BC) or a formulation containing a matched level of blue covarine and FD&C Blue No.1 (BC + D). The colour of the specimens were measured in vitro using a colorimeter, before and after brushing and changes in CIELAB and tooth Whiteness Index (WIO) values calculated. In a double-blind cross-over clinical study, subjects brushed with BC toothpaste, a toothpaste containing increased levels of blue covarine (BC + ) or BC + D toothpaste and tooth colour changes were measured with a digital image analysis system. Results: The in vitro study demonstrated that BC + D gave a significantly (p = 0.002) greater change in WIO value than BC. Clinical results showed that BC, BC+ and BC + D gave a significant increase in WIO (p < 0.0001) from baseline. The WIO change was significantly greater when brushing with BC + D toothpaste than with either toothpaste BC (p < 0.0001) or BC+ (p < 0.05). Conclusions: Toothpastes containing blue covarine or a combination of blue covarine and FD&C Blue No. 1 gave a statistically significant improvement in tooth whiteness immediately after brushing in both in vitro and clinical studies. In addition, the toothpaste containing both blue covarine and FD&C Blue No. 1 gave statistically significant greater tooth whitening from baseline than the blue covarine containing toothpastes. Clinical significance: The silica-based toothpastes containing blue covarine or a combination of blue covarine and FD&C Blue No. 1 evaluated in the current study gave significant tooth whitening benefits immediately after one brush.